Life Skills Implementation Program for Orphans from A Sociological Perspective at The Harapan Jitra Orphanage in Bengkulu City - Ezi Febriani; Purwaka Purwaka; Ika Pasca Himawati (MASI Mandiri Edukasi, 2026)
Orphans often face limitations in acquiring life skills, social values, and independence because they do not grow up in a complete family environment. This condition raises questions about how effectively orphanages can function as social institutions in preparing children to live independently in society. This study aims to analyze the effectiveness of implementing a life skills program for orphans at the Harapan Jitra Orphanage in Bengkulu City from a sociological perspective, particularly in terms of socialization, value internalization, and children's social integration. The research employed a qualitative, descriptive approach. Data were collected through participant observation and in-depth interviews with the orphanage's head, caregivers, foster children, and alumni, as well as through document analysis to strengthen empirical findings. Data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results show that the life skills program at Harapan Jitra Orphanage is quite effective in fostering children's independence both socially and functionally. Through routine daily activities, vocational training, productive work, and spiritual guidance, the orphanage serves as a secondary socialization agent, replacing the family's role in instilling discipline, responsibility, cooperation, and a work ethic. Children not only gain basic and vocational skills but also experience positive changes in attitudes, social identity, and adaptive abilities in broader society. Based on Talcott Parsons' AGIL framework, the program fulfills adaptation, goal attainment, integration, and latency functions. Nevertheless, effectiveness is constrained by limited funding, professional staff, and training facilities. Overall, the program contributes to preparing orphans to be independent and socially integrated individuals.